Preparation and characterization of rice gels containing tooth bleaching agent - Adchareeya Kaewpinta (2018)
In the present study, the modified white rice of Jasmine (JM) and Saohai (SH) were used to prepare the rice gels. Carbamide peroxide (CP) containing rice gels (CP rice gels) of JM (CP-JM) and SH (CP-SH) were prepared. The rice gels and CP rice gels show homogenous texture. Rice variety influences the characteristics and properties of the rice gels. Amylose content of JM was lower than SH. Rheological behavior of JM and CP-JM was pseudoplastic without thixotropy whereas that of SH and CP-SH was pseudoplastic with thixotropy. CP-SH showed higher adhesive property and viscosity than CP-JM whereas CP-JM showed faster in vitro drug release than CP-SH. For ex vivo efficacy evaluation, 55 normal human teeth were subjected to the CP rice gels. Samples were applied on tooth surface according to the dental bleaching techniques. For at-home bleaching technique, the CP rice gels with 10% and 20% CP were used with bleaching time of 8h and 4h, respectively. For in-office bleaching technique, the CP rice gels with 35% CP was used with bleaching time of 1 h. The developed CP rice gels showed significantly higher efficacy than the positive and negative controls. For at-home bleaching technique, CP-SH was the most effective gels whereas for in-office bleaching technique, CP-JM was the most effective gels.